Flexicurity — propagowanie elastycznych form zatrudnienia w ujęciu językowym i prawniczym - Olejniczak, Elwira; Kukieła, Beata (Acta Universitatis Lodziensis. Folia Linguistica, 2012)
This article discusses flexicurity, which is a very important and popular issue nowadays. The term flexicurity is used to characterize a successful combination of adaptability to a changing international environment and a solidarity welfare system, which protects the citizens from the brutal consequences of structural change. It is also presents how the Polish media and Polish employers view flexicurity. There is a strong demand in Poland to make labour markets, employment and work organization more flexible. It is important to make Polish employers and government remember that at the same time that there is an equally strong demand for providing security to employees and for preserving social cohesion in the society.